Pollution Threat by Face Mask after COVID-19 in Nepal - Kattel, P.; Chalise, R.; Adhikari, A.; Khanal, R. (Journal of Nepal Physical Society, 2023)
The COVID-19 pandemic has led to a significant increase in the production and use of disposable face masks, contributing to the growing global waste problem. While face masks were initially used primarily by healthcare professionals who knew how to dispose of them properly, their widespread adoption by the general public has raised concerns regarding the correct management of discarded masks. This issue is particularly significant as new types of pollutants, including microplastics, are being introduced into the environment. In underdeveloped nations like Nepal, misconceptions about the composition of face masks and a lack of awareness about their environmental impact are prevalent. To gain insight into the particle constituents of commonly used face masks, namely normal, surgical, and KN95 masks favored by residents of Nepal's Kathmandu Valley, we conducted Fourier Transform Infrared Spectroscopy (FTIR) analysis using an IRTracer-100 spectrometer. Our analysis identified the functional group and revealed that the primary material found in these masks is polypropylene microplastic polymers, rather than biodegradable fibers.